(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2026)
Microplastic pollution is now a lasting environmental problem. It affects the health of ecosystems and the health of humans. This review synthesizes current knowledge on the sources, environmental distribution, exposure pathways, and biological effects of microplastics across aquatic, terrestrial, and atmospheric systems. Primary microplastics are made on purpose for industry and consumer uses. Secondary microplastics form when big pieces of plastic break down. Both primary and secondary microplastics appear in water, soil, air, food and biological samples. In the water animals and the land animals microplastics often cause trouble eating, slower growth, cell damage from chemicals, inflammation and damage, to tissues. At the cell and molecule level microplastics can kill cells and damage DNA. Microplastics also disturb the system and change how genes work. The ability to adsorb and transport co occurring contaminants, like metals and persistent organic pollutants makes the contaminants more toxic. The human exposure comes mainly from eating and breathing. The ability to hold onto and move contaminants, such, as heavy metals and persistent organic pollutants creates combined and joint biological effects. The human exposure happens mainly through eating or breathing some microplastics and that interpret found microplastics in stool, blood, and placental tissues. The microplastics risks include cell damage, swelling, hormone disruption and buildup of chemicals.